2007
DOI: 10.1530/rep-07-0086
|View full text |Cite
|
Sign up to set email alerts
|

p53 regulates cyclophosphamide teratogenesis by controlling caspases 3, 8, 9 activation and NF-κB DNA binding

Abstract: The tumor suppressor protein p53 regulates the sensitivity of embryos to such human teratogens as ionizing radiation, diabetes, and cytostatics. Yet, the molecular mechanisms whereby it fulfills this function remain undefined. We used p53 heterozygous (p53 C/K ) female mice mated with p53 C/K males and then exposed to cyclophosphamide (CP) to test whether caspases 3, 8, and 9 and the transcription factor nuclear factor (NF)-kB may serve as p53 targets. Mice were exposed to CP on day 12 of pregnancy and killed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 44 publications
2
21
0
1
Order By: Relevance
“…In vivo, p53 activation in experimentally diabetic adult animals, as well as in embryo of pregnant diabetic rats, has been previously documented [30][31][32][33][34]. Upregulation of p53 was found associated with enhanced nonrenal [30] and renal cell [32][33][34] apoptosis.…”
Section: Discussionmentioning
confidence: 72%
“…In vivo, p53 activation in experimentally diabetic adult animals, as well as in embryo of pregnant diabetic rats, has been previously documented [30][31][32][33][34]. Upregulation of p53 was found associated with enhanced nonrenal [30] and renal cell [32][33][34] apoptosis.…”
Section: Discussionmentioning
confidence: 72%
“…By inducing the release of mitochondrial cytochrome-c, p53 might be able to activate effector caspases, including caspase-3. Caspase-3, -8, and -9 may be the apoptotic effector machinery engaged by p53 to mediate teratogen-induced apoptotic pathways (Takaoka et al, 2003;Pekar et al, 2007).…”
Section: 9655 Roles Of P53 and Caspases In Induction Of Apoptosis Inmentioning
confidence: 99%
“…Our recent study revealed that CP-induced excessive apoptosis is also mediated by p53 and, importantly, that p53 mediates CP-induced suppression of NF-κB DNA binding [91]. These data suggest that Loeken's model can legitimately be used to explain both diabetes-induced suppression of NF-κB activity and the function of TNFα as a protector against diabetes-induced teratogenic stress.…”
Section: Possible Mechanisms Underlying the Tnfα-regulated Response Tmentioning
confidence: 86%